Adme properties prediction of 5-phenyl-5,6-dihydrotetrazolo[1,5-c] quinazolines - Antypenko, O. M.; Antypenko, L.; Kalnysh, D.; Kovalenko, S. I.; Антипенко, Олексій Миколайович; Коваленко, Сергій Іванович (My University, 2022)
Due to the recent predicted affinity of 13 novel 5-phenyl-5,6-dihydrotetrazolo[1,5-c]-quinazolines to the ribosomal 50S protein L2P (2QEX) by molecular docking, their ADME properties were calculated at the site SwissADME to predict their drug-likeness. Hence, substances 6, 10, and 12 appeared to be the leading compounds among all studied ones and are of definite interest for further in vitro antimicrobial activity investigation.
Antypenko O. M. - https://orcid.org/0000-0002-8048-445X; Kovalenko S. I. - https://orcid.org/0000-0001-8017-9108.
Keywords: ADME properties; 5-phenyl-5,6-dihydrotetrazolo[1,5-c]quinazolines; drug-likeness